Taboos on Satu Suro Night in the Javanese Community of Karya Indah Village, Kampar Regency: An Islamic Aqidah Perspective - Muhammad Dandi Kurnia; Wilaela Wilaela; Sukiyat Sukiyat (Kutubkhanah, 2025)
This studyexaminesthe practice oftaboos observedon the eve of Satu Suro among the Javanese community in Karya Indah Village, Kampar Regency, from the perspective of Islamic Aqidah. Theresearch employs adescriptive qualitativemethod, utilizingobservation, interviews, and documentation techniques. Thefindingsindicate that the Javanese community in Karya Indah Villageregardsthe eve of Satu Suro as a special time,during whichtheyobserveseventaboos: refraining fromholding parties,avoidingharshlanguage,not eating dinner outside the home, not wasting staple foods,abstaining fromintimaterelations betweenhusband and wife, not buildinghouses,and not cleaning heirlooms without prayer. From the perspective of Islamic Aqidah, these taboos are considered inappropriate andpotentially contradictorytothe principle ofmonotheism. However, from a culturalstandpoint,the taboo tradition of Satu Suro Night reflects the local wisdom of the Javanese people in maintaining a balance between spirituality, social ethics, and respect for ancestors. This research contributes toa deeperunderstanding that Islam does not reject local culture as long as it does not conflict with the principles of Aqidah.Effortsaremadetoharmonizethe preservation of traditionswithspiritual valuealongsidethe Islamic Aqidah and identity of the Javanese Muslim community in Karya Indah Village. Satu Suro Night ismarked byactivities such asbeginning-and end-of-year prayers, tauhidrecitations, and TablighAkbar heldin mosques and prayer rooms. Thecustoms associated with the tabooson Satu Suro Nightemphasize prohibitions againstshedding blood, using harsh language, cursing, andlying.This studyexaminesthe practice oftaboos observedon the eve of Satu Suro among the Javanese community in Karya Indah Village, Kampar Regency, from the perspective of Islamic Aqidah. Theresearch employs adescriptive qualitativemethod, utilizingobservation, interviews, and documentation techniques. Thefindingsindicate that the Javanese community in Karya Indah Villageregardsthe eve of Satu Suro as a special time,during whichtheyobserveseventaboos: refraining fromholding parties,avoidingharshlanguage,not eating dinner outside the home, not wasting staple foods,abstaining fromintimaterelations betweenhusband and wife, not buildinghouses,and not cleaning heirlooms without prayer. From the perspective of Islamic Aqidah, these taboos are considered inappropriate andpotentially contradictorytothe principle ofmonotheism. However, from a culturalstandpoint,the taboo tradition of Satu Suro Night reflects the local wisdom of the Javanese people in maintaining a balance between spirituality, social ethics, and respect for ancestors. This research contributes toa deeperunderstanding that Islam does not reject local culture as long as it does not conflict with the principles of Aqidah.Effortsaremadetoharmonizethe preservation of traditionswithspiritual valuealongsidethe Islamic Aqidah and identity of the Javanese Muslim community in Karya Indah Village. Satu Suro Night ismarked byactivities such asbeginning-and end-of-year prayers, tauhidrecitations, and TablighAkbar heldin mosques and prayer rooms. Thecustoms associated with the tabooson Satu Suro Nightemphasize prohibitions againstshedding blood, using harsh language, cursing, andlying.